Composite metal oxide magnesium-based material, preparation method and application thereof
Patent Information
- Application Number
- CN202411158965.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-22
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-08-22
AI Technical Summary
[0005]综上所述,现有的镁基材料在吸放氢过程中存在吸放氢动力学缓慢、吸放氢温度高及循环稳定性差
[0030]第一:作为催化剂的棱柱状CeO2在机械合金化过程中基于其棱柱状的特殊形貌,在机械合金化中基于其氧化物质地坚硬,有助于研磨,并在研磨过程中附着在逐渐细化的Mg颗粒上,将镁颗粒分隔开,具有优越的细化效果和抑制团聚效应的作用。通过这种棱柱状的特殊形貌的CeO2球磨,可以极大地减小最终生成的复合镁基材料的尺寸,在球磨后使得镁基复合材料平均粒径d50约为1.26μm,d90约为2.78μm,并且制备工艺简单,操作过程简洁。
Smart Images

Figure CN118929575B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of hydrogen storage materials technology, specifically relating to a composite metal oxide magnesium-based material, its preparation method, and its application. Background Technology
[0002] With the continuous growth of global energy demand and the increasing prominence of environmental problems, the development and utilization of clean energy has become a critical issue that urgently needs to be addressed. Hydrogen energy has gradually attracted widespread attention due to its advantages such as zero emissions, high energy density, and renewability. However, the large-scale application of hydrogen energy still faces technological bottlenecks in the efficient storage and transportation of hydrogen. Currently, hydrogen storage methods mainly include high-pressure gaseous storage, cryogenic liquid storage, and solid-state hydrogen storage. Among these, while high-pressure gaseous hydrogen storage and cryogenic liquid hydrogen storage are relatively mature technologies, they suffer from drawbacks such as safety issues, high energy consumption, and limited storage density. In contrast, solid-state hydrogen storage, due to its high hydrogen storage density and better safety, has become a hot research area.
[0003] Among solid-state hydrogen storage materials, magnesium-based hydrides are favored due to their abundant resources, high hydrogen storage capacity, and good safety. However, magnesium-based materials suffer from slow hydrogen absorption and desorption kinetics, high absorption and desorption temperatures, and poor cycle stability during hydrogen absorption and desorption, which limit their practical applications.
[0004] To address these issues, researchers have proposed various modification strategies, among which metal oxide composite modification is an effective method. N.S. Mustafa et al. (10.1016 / j.jallcom.2016.11.158) studied the hydrogen absorption and desorption properties of CeO2-doped MgH2, but their work did not adequately optimize the microstructure of the material and failed to fully utilize the interfacial and nano-effects of CeO2.
[0005] In summary, existing magnesium-based materials suffer from slow hydrogen absorption / desorption kinetics, high hydrogen absorption / desorption temperatures, and poor cycle stability during hydrogen absorption / desorption. Summary of the Invention
[0006] To overcome the problems existing in the prior art, the present invention aims to provide a composite magnesium oxide-based material, its preparation method, and its application. The prismatic morphology of the composite magnesium oxide-based material obtained by CeO2 ball milling can greatly reduce the size of the final composite magnesium-based material. By optimizing the microstructure and composition of the material, its hydrogen storage performance can be improved.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A composite metal oxide magnesium-based material, namely MgH2-CeO2 (prismatic), wherein the content of Mg is 90-95 wt.% and the content of CeO2 is 5-10 wt.%, and the specific surface area of the prismatic CeO2 is 77.682 m². 2 / g, the prismatic CeO2 has a size of 200-550nm.
[0009] The prismatic CeO2 is formed by the nucleation and aggregation of cerium particles of 30-600nm over time during a hydrothermal process. The thickness of the prism is about 200-300nm and the side length is about 200-550nm. During the mechanical mixing process, due to the hardness of the oxide, it impacts and collides with the grinding balls during the ball milling process, resulting in repeated cold welding and fracture. Compared with CeO2 of ordinary morphology, it is more conducive to refining grains and suppressing agglomeration effect.
[0010] A method for preparing a composite metal oxide magnesium-based material includes the following steps;
[0011] Step 1: Preparation of prismatic CeO2:
[0012] Using cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and urea as raw materials, the aqueous solution of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and urea is added to a stainless steel autoclave lined with polytetrafluoroethylene, and then sealed for hydrothermal synthesis.
[0013] The precipitate was filtered and then washed with deionized water to obtain CeO2 material. The obtained CeO2 material was calcined in air to obtain prismatic CeO2.
[0014] The hydrothermal method for preparing CeO2 with special morphology mainly uses urea as a precipitant and cerium nitrate hexahydrate (Ce(NO3)3·6H2O) as a metal precursor solution. By changing the urea concentration, the acidity or alkalinity of the solution is altered, thereby affecting the nucleation process of the material. The higher hydrothermal temperature promotes the formation of CeO2 from the hydration products through a dissolution-recrystallization mechanism.
[0015] Step 2: Mechanical alloying modification:
[0016] Magnesium powder with a purity ≥ 99.8% and prismatic CeO2 prepared in step one were selected, weighed in a glove box, and then placed into a high-energy ball mill jar for ball milling; finally, Mg-CeO2 (prismatic) was obtained.
[0017] Step 3: Preparation of MgH2-CeO2 (prismatic shape):
[0018] The Mg-CeO2 (prismatic) obtained in step 2 was placed in a hydrogenation reactor under an inert atmosphere to obtain MgH2-CeO2 (prismatic).
[0019] In step 1, the hydrothermal synthesis conditions are as follows: synthesis time is 2-24 h; synthesis temperature is 120-180 ℃; urea concentration is 0.0375-0.15 g / mL; Ce(NO3)3·6H2O concentration is 0.025-0.25 g / mL.
[0020] The obtained CeO2 material was calcined in air at 400-600℃ for 2-4 hours.
[0021] In step 2, the Mg:CeO2 ratio is 9:1, and the ball-to-material ratio is 40:1-30:1. The ball mill jar is first flushed 2-3 times under 0.2 MPa hydrogen pressure, then pressurized to 0.4-0.5 MPa and placed into the ball mill. The mill operates at 600-1000 rpm, with a cycle of 5 minutes forward, 5 minutes intermittent, 5 minutes reverse, and 5 minutes intermittent, for a total cycle of 20 minutes, continuing for 10-12 hours. During this period, the ball mill jar is replenished with gas every 2 hours. Finally, Mg-CeO2 (prismatic shape) is obtained, with a final average particle size d. 50 =1.26μm, d 90 =2.78μm.
[0022] In step 2, after high-energy ball milling and mechanical alloying, the particle size of the composite metal oxide magnesium-based hydrogen storage material powder after sieving is ≤2.78μm.
[0023] In step 3, the chamber is cleaned with hydrogen gas at a hydrogen pressure of 0.2 MPa 2-3 times before heating. The temperature is increased at a hydrogen pressure of 2-4 MPa, with an average heating rate of 5-10℃ / min, until the temperature reaches 300-380℃. The hydrogen pressure is 4-6 MPa, and the temperature is maintained for 8-10 hours. After the reaction is completed, the furnace is cooled to room temperature.
[0024] In step 3, during the mechanical alloying modification process in step 2, the long-term, high-speed ball milling in a hydrogen atmosphere will slightly reduce some Ce on the obtained Mg-CeO2. After step 3, a small amount of CeH2 will be generated in situ on the obtained MgH2-CeO2 (prismatic shape). 2.73 .
[0025] The composite metal oxide magnesium-based material is used for hydrogen storage. With the composite metal oxide magnesium-based material as the hydrogen storage material and the metal oxide CeO2 as the catalyst, the high-valence metal in the metal oxide is reduced to a low-valence state during the hydrogen absorption and desorption process, thereby forming a diffusion channel for hydrogen atoms. During the addition process, mechanical alloying can introduce various defects such as vacancies, dislocations and stacking faults, thereby increasing the free energy of the magnesium-based hydrogen storage material and improving the hydrogen absorption and desorption kinetics performance of the magnesium-based hydrogen storage material.
[0026] During hydrogen absorption, hydrogen molecules are first adsorbed and dissociated into hydrogen atoms on the material surface, followed by high-valence metal ions such as Ce in the metal oxide.4+ When it comes into contact with hydrogen, it undergoes a reduction reaction and is reduced to the lower valence metal ion Ce. 3 + This reduction process releases oxygen vacancies or defect sites, forming channels for hydrogen atom diffusion within the material. These diffusion channels form a "network" within the material, making it easier for hydrogen atoms to move within the material and thus accelerating hydrogen diffusion. This mechanism significantly increases the material's hydrogen absorption rate.
[0027] Mechanical alloying is a commonly used method in the entire material preparation process. Through mechanical means such as high-energy ball milling, metallic magnesium and metal oxides are thoroughly mixed at the nanoscale. This process not only physically bonds the two substances but also introduces a large number of lattice defects, such as vacancies, dislocations, and stacking faults, into the material. The presence of these defects increases the material's free energy, making it easier for hydrogen atoms to overcome the energy barrier during hydrogen absorption and desorption, thus accelerating the process. Furthermore, these defects can also serve as hydrogen atom trapping sites, further enhancing the material's hydrogen storage capacity.
[0028] Magnesium-based composite metal oxide materials have broad application prospects in fields such as hydrogen fuel cells, solid-state hydrogen storage devices, and renewable energy storage, providing an efficient and safe solution for the future development and utilization of hydrogen energy.
[0029] The beneficial effects of this invention are:
[0030] First, prismatic CeO2, acting as a catalyst, benefits from its unique prismatic morphology during mechanical alloying. Its hard oxide texture facilitates grinding, and during this process, it adheres to the gradually refined Mg particles, separating them and exhibiting superior refining effect and inhibiting agglomeration. Ball milling of this prismatic CeO2 can significantly reduce the size of the final magnesium-based composite material, resulting in a higher average particle size d of the magnesium-based composite material after ball milling. 50 Approximately 1.26 μm, d 90 It is approximately 2.78 μm in size, and the preparation process is simple and the operation is straightforward.
[0031] Second: During the mechanical alloying process, the metal oxide CeO2 is introduced to form trace amounts of CeH in the final material. 2.73 The CeO2 forms a "hydrogen pump" effect with MgH2, which is beneficial to the thermodynamics of hydrogen absorption and desorption. Some CeO2 is embedded on the surface of the Mg matrix during ball milling, providing an auxiliary diffusion channel for hydrogen.
[0032] Third: The formed CeH 2.73This lowers the energy barrier of the hydrogen storage material, thereby reducing the apparent activation energy of the hydrogen absorption / desorption reaction of the magnesium-based hydrogen storage material and improving its hydrogen storage performance. Attached Figure Description
[0033] Figure 1 SEM and XRD diffraction patterns of the prepared prismatic CeO2.
[0034] Figure 2 This is a statistical chart of the particle size of the magnesium-based hydrogen storage material after 12 hours of alloying.
[0035] Figure 3 SEM and XRD patterns of the magnesium-based composite metal oxide hydrogen storage material. Detailed Implementation
[0036] The present invention will now be described in further detail with reference to the accompanying drawings.
[0037] Example 1
[0038] Magnesium powder with a purity ≥ 99.98% and prismatic CeO2 were selected. 1.8g of Mg powder and 0.2g of prismatic CeO2 were weighed in an inert gas and then loaded into a high-energy ball mill jar. The ball-to-material ratio was 30:1. The ball mill jar was flushed with hydrogen 2-3 times under 0.2 MPa hydrogen pressure. After pressurizing the jar with hydrogen at 0.4 MPa, it was placed in a ball mill and milled at 600 rpm with a cycle of 5 min forward, 5 min intermittent, 5 min reverse, and 5 min intermittent, for 20 min, for a total of 12 h. During this period, the jar was replenished with hydrogen every 2 h. The resulting Mg-CeO2 (prismatic) was placed in a hydrogenation reactor under an inert atmosphere. Before heating, the chamber was flushed with hydrogen 2-3 times under 0.2 MPa hydrogen pressure. The temperature was increased to 300 °C at an average rate of 5 °C / min, and held at 4 MPa hydrogen pressure for 8 h. After the reaction, the reactor was cooled to room temperature to obtain MgH2-CeO2 (prismatic), with an average size D. 90 =2.73μm.
[0039] The results show that the material exhibits significant performance improvement during hydrogen absorption and desorption. Compared with pure MgH2 material without CeO2 doping, the hydrogen absorption and desorption kinetics are greatly improved, the hydrogen absorption and desorption temperature is significantly reduced, and it also has excellent cycle stability and high hydrogen storage capacity. This indicates that the prepared MgH2-CeO2 (prismatic) material has broad application prospects in hydrogen energy storage applications.
[0040] Example 2
[0041] Magnesium powder with a purity ≥ 99.98% and prismatic CeO2 were selected. 0.95g of Mg powder and 0.05g of prismatic CeO2 were weighed in an inert gas and then loaded into a high-energy ball mill jar. The ball-to-material ratio was 35:1. The ball mill jar was flushed with hydrogen gas 2-3 times under a hydrogen pressure of 0.2 MPa. After pressurizing the ball mill jar with hydrogen gas at a hydrogen pressure of 0.45 MPa, it was placed in a ball mill and milled at a speed of 900 rpm. The milling process was repeated 20 minutes in a cycle of 5 min forward, 5 min intermittently, 5 min reverse, and 5 min intermittently, for a total of 12 hours. During this period, the ball mill jar was replenished with hydrogen gas every 2 hours. The resulting Mg-CeO2 (prismatic) was placed in a hydrogenation reactor under an inert atmosphere. Before heating, the chamber was flushed with hydrogen gas at a hydrogen pressure of 0.2 MPa 2-3 times. The temperature was increased at a hydrogen pressure of 2 MPa, with an average heating rate of 8 °C / min, until the temperature reached 350 °C. The hydrogen pressure was 5 MPa, and the temperature was held for 9 hours. Afterward, the temperature was cooled to room temperature with the furnace to obtain MgH2-CeO2 (prismatic).
[0042] The results show that the material exhibits significant performance improvement during hydrogen absorption and desorption. Compared with pure MgH2 material without CeO2 doping, the hydrogen absorption and desorption kinetics are greatly improved, the hydrogen absorption and desorption temperature is significantly reduced, and it also has excellent cycle stability and high hydrogen storage capacity. This indicates that the prepared MgH2-CeO2 (prismatic) material has broad application prospects in hydrogen energy storage applications.
[0043] Example 3
[0044] Magnesium powder with a purity ≥ 99.98% and prismatic CeO2 were selected. 2.76g of Mg powder and 0.24g of prismatic CeO2 were weighed in a glove box and then loaded into a high-energy ball mill jar. The ball-to-material ratio was 40:1. The ball mill jar was flushed with hydrogen 2-3 times under 0.2 MPa hydrogen pressure. After pressurizing the ball mill jar with hydrogen at 0.5 MPa hydrogen pressure, it was placed in a ball mill and milled at 1000 rpm with a cycle of 5 min forward, 5 min intermittent, 5 min reverse, and 5 min intermittent for 20 min, for 12 h. During this period, the ball mill jar was replenished with gas every 2 h. The resulting Mg-CeO2 (prismatic) was placed in a hydrogenation reactor under an inert atmosphere. Before heating, the chamber was flushed with hydrogen at 0.2 MPa hydrogen pressure 2-3 times. The temperature was increased at 2 MPa hydrogen pressure with an average heating rate of 10 °C / min, and the temperature was increased to 380 °C. The hydrogen pressure was 6 MPa, and the temperature was held for 10 h. After that, it was cooled to room temperature with the furnace to obtain MgH2-CeO2 (prismatic).
[0045] The results show that the material exhibits significant performance improvement during hydrogen absorption and desorption. Compared with pure MgH2 material without CeO2 doping, the hydrogen absorption and desorption kinetics are greatly improved, the hydrogen absorption and desorption temperature is significantly reduced, and it also has excellent cycle stability and high hydrogen storage capacity. This indicates that the prepared MgH2-CeO2 (prismatic) material has broad application prospects in hydrogen energy storage applications.
[0046] like Figure 1 The image shows the SEM image and XRD diffraction pattern of the prismatic CeO2 prepared in this invention. The XRD diffraction pattern shows that the prepared prismatic CeO2 basically corresponds to the peak values of PDF card No. 16-4225. The SEM image clearly shows that the morphology of the prismatic CeO2 is triangular prism, with a size between 300-500 nm.
[0047] like Figure 2 The figure shows the average particle size distribution of Mg-xCeO2 (x = 5%-10%) material after 12 hours of mechanical alloying. It can be seen that the final average particle size d... 50 =1.26μm, d 90 =2.78μm, which basically achieves the goal of refining MgH2.
[0048] like Figure 3 The image shows the SEM and XRD diffraction patterns of the final prepared MgH2-xCeO2 (x = 5%-10%). The XRD diffraction pattern reveals the presence of MgH2 and trace amounts of CeH2 in the material. 2.73 This explains CeH 2.73 With the presence of MgH2.
[0049] In this invention, mechanical alloying is a solid-state reaction in which metal and alloy powders, under oxygen-free conditions, undergo repeated cold welding and fracture through impact and collision with grinding balls in a high-energy ball mill, thereby obtaining alloyed powders. This reaction can form a second phase, such as CeH₂. 2.73 This reduces the activation energy of hydrogen absorption and desorption, improves thermodynamics, and allows for mechanical alloying in a hydrogen atmosphere, where hydrogen acts as both a protective atmosphere and a pre-hydrogenation process. Adding CeO2 during mechanical alloying benefits from its hard oxide properties, aiding in grinding and adhering to the gradually refined Mg particles, thus separating the particles, refining the grain size, and suppressing agglomeration. Furthermore, during high-energy ball milling, CeO2 in a hydrogen atmosphere can in situ reduce trace amounts of CeH2 onto Mg. 2.73 Its "hydrogen pump" effect with MgH2 is more conducive to the hydrogen absorption and desorption kinetics.
[0050] This invention optimizes the preparation method and mechanical alloying process of CeO2 to form a prismatic CeO2 structure, utilizing its high specific surface area and unique morphology to improve the hydrogen absorption and desorption performance of magnesium-based materials. Furthermore, by optimizing the ball milling and hydrogenation processes, the hydrogen storage capacity and cycle stability of the material are further enhanced.
Claims
1. A composite metal oxide magnesium-based material, namely MgH2-CeO2, wherein the content of Mg is 90-95 wt.% and the content of CeO2 is 5-10 wt.%, wherein the specific surface area of the prismatic CeO2 is 77.682 m². 2 / g, the prismatic CeO2 has a size of 200~550nm.
2. The composite metal oxide magnesium-based material according to claim 1, characterized in that, The prismatic CeO2 is formed by the nucleation and condensation of cerium particles of 30-600 nm over time during a hydrothermal process. The thickness of the prism is 200-300 nm and the side length is 200-550 nm.
3. A method for preparing a composite metal oxide magnesium-based material according to claim 1 or 2, characterized in that, Includes the following steps; Step 1: Preparation of prismatic CeO2: Using cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and urea as raw materials, the aqueous solution of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) and urea is added to a stainless steel autoclave lined with polytetrafluoroethylene, and then sealed for hydrothermal synthesis. The precipitate was filtered and then washed with deionized water to obtain CeO2 material. The obtained CeO2 material was calcined in air to obtain prismatic CeO2. Step 2: Mechanical alloying modification: Magnesium powder with a purity ≥ 99.8% and prismatic CeO2 prepared in step 1 were selected, weighed in a glove box, and then placed into a high-energy ball mill jar for ball milling; finally, Mg-CeO2 was obtained. Step 3: Preparation of MgH2-CeO2: The Mg-CeO2 obtained in step 2 was placed in a hydrogenation reactor under an inert atmosphere to obtain MgH2-CeO2.
4. The method for preparing a composite metal oxide magnesium-based material according to claim 3, characterized in that, In step 1, the hydrothermal synthesis conditions are as follows: synthesis time is 2-24 h; synthesis temperature is 120-180 ℃; urea concentration is 0.0375-0.15 g / mL; Ce(NO3)3·6H2O concentration is 0.025-0.25 g / mL; The obtained CeO2 material was calcined in air at 400-600 °C for 2-4 h.
5. The method for preparing a composite metal oxide magnesium-based material according to claim 3, characterized in that, In step 2, the Mg:CeO2 ratio is 9:1, and the ball-to-material ratio is 40:1-30:
1. The ball mill jar is first flushed 2-3 times under 0.2 MPa hydrogen pressure, then pressurized to 0.4-0.5 MPa and placed into the ball mill. The mill operates at 600-1000 rpm, with a cycle of 5 min forward, 5 min intermittent, 5 min reverse, and 5 min intermittent, for a total cycle of 20 min, lasting 10-12 h. During this period, the ball mill jar is replenished with gas every 2 h. Finally, Mg-CeO2 is obtained, with a final average particle size d. 50 =1.26 μm, d 90 =2.78 μm.
6. The method for preparing a composite metal oxide magnesium-based material according to claim 3, characterized in that, In step 2, after high-energy ball milling and mechanical alloying, the particle size of the composite metal oxide magnesium-based hydrogen storage material powder after sieving is ≤2.78 μm.
7. The method for preparing a composite metal oxide magnesium-based material according to claim 3, characterized in that, In step 3, the chamber is cleaned 2-3 times with hydrogen gas at a hydrogen pressure of 0.2 MPa before heating. The temperature is increased at a hydrogen pressure of 2-4 MPa, with an average heating rate of 5-10 ℃ / min, until the temperature reaches 300-380 ℃. The hydrogen pressure is 4-6 MPa, and the temperature is maintained for 8-10 h. After the reaction is completed, the furnace is cooled to room temperature.
8. The method for preparing a composite metal oxide magnesium-based material according to claim 3, characterized in that, In step 3, during the mechanical alloying modification process in step 2, the long-term, high-speed ball milling in a hydrogen atmosphere will slightly reduce some Ce on the obtained Mg-CeO2. After step 3, a trace amount of CeH will be generated in situ on the obtained MgH2-CeO2. 2.73 .
9. The application of the composite metal oxide magnesium-based material according to claim 1 or 2, characterized in that, The composite metal oxide magnesium-based material is used for hydrogen storage. With the composite metal oxide magnesium-based material as the hydrogen storage material and the metal oxide CeO2 as the catalyst, the high-valence metal in the metal oxide is reduced to a low-valence state during the hydrogen absorption and desorption process, thereby forming a diffusion channel for hydrogen atoms. During the addition process, mechanical alloying can introduce various defects such as vacancies, dislocations and stacking faults, thereby increasing the free energy of the magnesium-based hydrogen storage material and improving the hydrogen absorption and desorption kinetics performance of the magnesium-based hydrogen storage material.
10. The application of the composite metal oxide magnesium-based material according to claim 9, characterized in that, During hydrogen absorption, hydrogen molecules are first adsorbed and dissociated into hydrogen atoms on the material surface, followed by high-valence metal ions such as Ce in the metal oxide. 4+ When it comes into contact with hydrogen, it undergoes a reduction reaction and is reduced to the lower valence metal ion Ce³. + This reduction process releases oxygen vacancies or defect sites, forming channels for hydrogen atom diffusion within the material. These diffusion channels form a "network" within the material, making it easier for hydrogen atoms to move within the material and thus accelerating hydrogen diffusion. This mechanism significantly improves the hydrogen absorption rate of the material.
Citation Information
Patent Citations
Magnesium-based hydrogen storage material and preparation method thereof
CN103526141A
Cerium oxide nano materials and its preparation and use
CN1840480A